Plastic ingestion by fish: A global assessment. (December 2019) - Azevedo-Santos, Valter M.; Gonçalves, Geslaine R.L.; Manoel, Pedro S.; Andrade, Marcelo C.; Lima, Felipe P.; Pelicice, Fernando M.
Graphical abstract: Image 1 Highlights: We compiled records of plastic ingestion by fishes around the world. We found reports of plastic ingestion for 427 fish species. Fishes of different environments ingested plastic. Most species were carnivore, but omnivores, herbivores, algivores, and detritivores also ingested plastics.